Inconsistency of Protected Rice Fields with Spatial Planning in Purworejo Regency - Khairullah, Naufal Zain; Agustyarsyah, Agustyarsyah; Setiowati, Setiowati (Sekolah Tinggi Pertanahan Nasional, 2025)
This study aims to analyze the discrepancy between Protected Rice Fields (LSD) and the Regional Spatial Plan (RTRW) in Purworejo Regency, its impact on land management and spatial planning, and formulate solutions. The method used is a mixed approach with spatial overlay analysis techniques and in-depth interviews with relevant stakeholders. The results of the analysis indicate significant discrepancies concentrated in Grabag and Pituruh Districts, with a clustered distribution pattern. This discrepancy results in potential land use conversion, licensing conflicts, and irregularities in the implementation of spatial planning policies. To address this problem, recommendations for updating spatial data based on field verification, improving coordination between agencies, and strengthening education and outreach to land management communities were made. This study concludes that aligning LSD and RTRW data is crucial for achieving sustainable regional spatial management and protecting agricultural land.